Kurikulum Pembelajaran Bahasa Arab Untuk Penutur Asing: Ragam Konsep Dan Desain Silabus - Rosyad, Muhammad Sabilar; Qomaruddin, Farid; Farih, Muhammad (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
This research aims to provide a perspective regarding several Arabic language learning curricula and the unique characteristics of it as well as patterns of use in designing Arabic language learning to non-native speakers. Researchers used a qualitative approach with a type of literature study. The data in this research comes from several books and scientific journals related to the topic, and the data is then analyzed using qualitative descriptive techniques. The results of this research are: 1) In the context of Arabic language learning, there are four types of curriculum that are frequently used in the process of teaching and learning Arabic to non-native speakers, namely; Grammatical Syllabus, Situational Syllabus, Notional Syllabus, and Multidimensional Syllabus. 2) That each type of curriculum plays an important role in the success of the Arabic language teaching and learning program in accordance with the desired objectives and perspectives, and all four have their respective strengths and weaknesses. Therefore, teachers must pay more attention to each characteristics before determining the type of curriculum they will use.